Impact of Toxoplasmosis in Im-mune Respons in Hemodialysis Patients - Salah Salem, Maysaloon; Jassim Shaker , Mohammed; Khalid Mohammed , Nabil (Diyala Journal of Medicine, 2022)
Background: Toxoplasma gondii is the most common infection of protozoa, affecting a wide range of hosts. Toxoplasmosis is usually asymptomatic in immunocompetent persons, but in immunocompromised persons (ex:patients on dialysis) significant problems can ensure, and may progress to a life-threatening infection. Objective: To investigate the seroprevalence of anti-Toxoplasma antibodies in patients undergoing hemodialysis in Baquba / Iraq . Patients and Methods: A group of blood samples, consisting of 75 dialysis patients and 50 healthy controls, were examined for the detection of anti-toxoplasma antibodies in Baquba Governorate from November 2020 to April 2021 using enzyme-linked immunosorbent assay (ELISA) for IgG and IgM. Results: The total numbers of the 125 samples were examined, 32 (44.0%) and 2 (4.0%) were IgG-positive for both patients and healthy individual respectively, and the results of the current study showed only 1 (1.33%) was seropositive IgM for patient group, while no seropositive healthy subjects was found for IgM . The results showed that the percentage of seropositivity was higher in 17 males (40.47%) than in females 15 (45.45%) in the group of patients, but the differences were not statistically significant . As for the age groups, a positive increase was observed in the age group 11-30 years when comparing patients and healthy people, as the percentage reached 5 (29.41%). It was also observed that the highest seropositivity in the education levels was in the group of patients at the educational level 6-12 (45.45%) than in the healthy controls group, but the differences were not statistically significant between education levels. Patients living in urban areas had significantly higher serum (P = 0.0041) than patients in rural areas, and the odds ratio was 22,000. And those who had contact with cats showed a significant increase in seropositivity p = 0.0466 and odds ratio was 20.5789. Conclusion: Dialysis patients are at risk for toxoplasmosis and should be screened on a regular basis to prevent the disease from spreading during hemodialysis.